Imperatives of Quality Insuring of the Production Cycle and EffectiveFunctioning Process of the Enterprises of Agro-Product Subcomplex of Ukraine - Vinichenko, I. I.; Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Kurbatska, L. M.; Polenenka, M. A.; Oleksiuk, V. O. (My University, 2020)
The article deals with the imperatives of quality insuring of the production cycle and the effective functioning process of the enterprises of agro-product subcomplex of Ukraine. An effective functional system has been built which, based on the quantitative and qualitative criteria of competitiveness of enterprises, determines the scale and effectiveness of their activity, provides opportunities to reproduce the resource potential of the agro-product subcomplex industries. The set of processes of relevant implication ‘resources – structure – efficiency – development of the system’ was singled out in order to improve the qualitative and quantitative properties of the production cycle as a creation of efficiency. An adaptive-renovation approach is proposed, which allows selecting from the system of indicators representative-effective indicators and factors of financial and resource load on the level of self-financing of the production cycle with 95% probability. The criterion of ‘optimal maximum profit’, which meets the requirements of a clear economic interpretation of the performance indicators, provides an increase in the value of cash flow to reduce the dependence of the entities of inter-economic relations on the slowdown in the self-financing of the production cycle. It is proved that the integration of agro-product industries with a long continuous cycle has specified functional changes in their efficiency. We have grouped the entities of inter-economic relations by the level of production cost and profitability of the sold products, which ensure the effective process of functioning of the enterprises of the agro-product subcomplex. The parameters of financial and resource load on indicators of self-financing of the production cycle of enterprises of poultry agro-complex in the average for one region of Ukraine are determined. Alternative business projects for the production of poultry products are proposed while changing the cash flow discount rate.
Keywords: economic activity; consumer value; agricultural sector; production; integration of economic relations